The Influence of Learning Motivation and Gender to Economic Learning Achievements Student Class X Madrasah Aliyah in Kampar Regency - Basuki Pramono; Almasdi Syahza; Gusnardi Gusnardi (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
The background of this research is the achievement of students 'economic learning which is still low and the students' economic achievement which is different in class X Madrasah AliyahNegeri Se Kampar Regency. Student learning achievement is still low by 65,4%, while female student equal to 51,9%. The still low and different learning achievement in this study is influenced by the learning motivation which is the internal factor, and the gender that is suspected of the tendency of different learning motivation and learning achievement of male and female students. This research aim to know the influence of learning motivation and gender to student achievement of class X Madrasah AliyahNegeri the Kampar regency.This research method using quantitative descriptive method. The population in this study were students of Madrasah Aliyah in Kampar regency with the number of 208 people with a total sample of 68 people with probability sampling technique with random sample sampling. Data obtained by observation and disseminate research questionnaire to the respondent. Data were analyzed by using descriptive percentage and statisticanalysis use multiple linear regression. Against the instrument tested the validity and reliability by using the alpha cronbach formula. The results showed that: 1) partially, there is a significant influence between the motivation of learning on student economic achievement with a t value of 6.443 sig. < 0.05. 2) Partially (chi square) there is no significant influence between gender on learning achievement with sig. > 0.05. the tendency of higher learning motivation of male students than female students. Similarly, the students' economic achievement tend to be higher than female students. 3) simultan, there is a significant influence of learning and gender motivation on economic learning achievement with multiple linear regression equation Y = 25,981 + 0,806X1 + -0,773X2 + ɛn. From result of F value equal to 20,821 with sig. 0,000 <0.05 means that learning and gender motivation has an influence on economic learning achievement. And a large contribution to the model by 39%. From these results can be concluded that to improve the achievement of economic learning can be done by improving students' learning motivation and not discriminate between male students or female students.